Childhood Memories in Eating Disorders: An Explorative Study Using Diagnostic Imagery - Basile, Barbara; Novello, Chiara; Calugi, Simona; Dalle Grave, Riccardo; Mancini, Francesco (Frontiers in Psychology, 2021)
Together with socio-cultural components, the family environment and early parent-child interactions play a role in the development of eating disorders. The aim of this study was to explore the nature of early parent-daughter relationships in a sample of forty-nine female in-patients with an eating disorder. To acquire a detailed image description of the patient’s childhood experiences we used diagnostic imagery, a Schema Therapy-derived experiential technique. This procedure allows exploring specific contents within the childhood memory (i.e., emotions and unmet core needs), bypassing rational control, commonly active during direct verbal questioning. Additionally, patients completed self-report measures to assess for eating disorder severity, general psychopathology, and individual and parental schemas pervasiveness. Finally, we explored possible differences in the diagnostic imagery content and self-report measures in two subgroups of patients with anorexia nervosa and bulimia nervosa. Results showed that the most frequently reported unmet needs within patients’ childhood memories were those of safety/protection, care/nurturance, and emotional expression, referred specifically to the maternal figure. Overall, mothers were described as more abandoning, but at the same time particularly enmeshed in the relationship with their daughters. Conversely, patients perceived their fathers as more emotionally inhibited and neglecting. Imagery-based techniques might represent a powerful tool to explore the nature of early life experiences in eating disorders, allowing a more detailed case conceptualization and addressing intervention on early-life vulnerability aspects in disorder treatment.